CRACKING THE CODE TO SHOPEE PURCHASES: ANALYZING THE INFLUENCE OF REVIEW CONTENT AND E-SERVICE QUALITY ON USER PURCHASE DECISION IN MANADO CITY - Viona Echaristy Haluti; James D. D. Massie; Emilia M. Gunawan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
This study explores how review content and e-service quality influence Shopee user purchase decisions. Previous research highlighted factors like product quality, price, trust, and website usability affecting online purchases. Reviews offer social proof of a product's worth, but their impact depends on content, volume, and sentiment. E-service quality includes website design, responsiveness, security, and support, shaping the online experience. The results of this study are in accordance with Ichsan (2018) view that the better someone's Review Content, the better the store's Purchase Decision. This study found that Review Content and E-Service Quality have a positive influence on Purchase Decision in the Shopee application, with a magnitude of 0.914. The percentage of Review Content and E-Service Quality can explain Purchase Decision in the Shopee application by 91.4%, while the remaining 8.6% is influenced by other variables.   Keyword: purchase decision, e-service quality, review content